Effects of DEM resolution and source on hydrological modeling - Hanuphab,T. (2015)
Digital Elevation Model (DEM) has been widely used in hydrological model. The accuracy of hydrological model depends on the source and resolution of DEM data. This study investigated the effects of DEMs on deriving topographic and hydrological attributes. Two DEMs at four resolutions including 5m, 10m, 20m, and 30m were prepared and tested for generating stream network and watershed area in Phuket Province, Thailand. Contour line interval 5 m and GDEM resolution 30 m were used in this study. Using higher resolution DEMs can derive more accurate stream network, but highest resolution data may not necessarily offer the best results, depending on the resolutions selected to compare the extracted networks. DEM resolution may have minor different impacts but the significantly different is DEM data source.